Macbeth - Stewart, Diana; Shaw, Charles, 1941-2005; Shakespeare, William, 1564-1616. (Milwaukee : Raintree Publishers, 1982)
An adaptation of the tragedy of prophecy and royal murder set in medieval Scotland.
Keywords: Macbeth, -- King of Scotland, -- active 11th century -- Juvenile drama; Regicides -- Juvenile drama; Plays; Scotland -- Juvenile drama; Scotland -- History -- To 1057 -- Drama; Tragedies